Supplementary material 1. Microdalyellia n. sp. 3D representation of genital system from confocal stack images (54 pictures) - Arias, Abril Agustina (2025)
Supplementary material 1. Microdalyellia n. sp. 3D representation of genital system from confocal stack images (54 pictures), (Video mp4). The reference colors used to show the organs in the 3D Model are: Abductor muscles of the stylet (burgundy), circular muscle fibers surrounding the stylet (orange), common genial atrium (blue), copulatory bursa (light blue), female duct (brown), granular vesicle (red), gonopore (green), retractor muscles of the stylet (light green), ss1 (yellow), ss2 (grey), seminal vesicle (violet), seminal receptacle (lilac), uterus (dark pink), protractor muscles of both common genital atrium and gonopore (light pink).